Partisipasi Masyarakat dalam Pembangunan Sanitasi Berbasis Masyarakat di Kelurahan Perawang Kecamatan Tualang - Regina Safitri; Mayarni Maya (Journal of Social and Policy Issues, 2021)
Sanitation problems in Perawang Village are still relatively lagging behind. Many people do not have access to proper sanitation. The Community-Based Sanitation Program (SANIMAS) is the provision of government assistance funds as a form of initiative to provide facilities and infrastructure for wastewater that is responsive to needs. In this program, community participation is also an important point where when the community takes part in development, they will feel satisfied when they see the results of the SANIMAS development in Perawang Village. The purpose of this study was to determine community participation in community-based sanitation development in Perawang Village, Tualang District and to determine the inhibiting factors for community participation in Perawang Village, Tualang District. The theory used in this study is the participation theory of Dwiningrum in Sombang which uses four indicators, namely participation in decision making, participation in implementation, participation in benefit making, and participation in evaluation. The method that the researcher uses is a qualitative method using a descriptive approach. In this qualitative study, the authors analyze on the basis of research problems using data collection techniques in the form of interviews, observations and documentation. The results of this study indicate that community participation in community-based sanitation development in Perawang Village, Tualang District can be said to be active. The obstacle for this program is the work of the community and is also constrained by the Covid-19 condition.